Electrolyte, secondary battery, and device

By using lithium fluorosulfonimide containing lithium and specific types of linear carbonate and fluorolinear ether as components of the electrolyte, the problems of calendar life and thermal runaway of lithium-ion batteries under high temperature conditions are solved, and the battery performance is significantly improved, including calendar life, safety performance, fast charging performance and thermal stability.

CN119852525APending Publication Date: 2025-04-18NIO TECH ANHUI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510037805.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Existing lithium-ion batteries cannot effectively improve calendar life and thermal runaway under high temperature conditions, mainly because the cyclic carbonate is unfriendly to the negative electrode material and the narrow electrochemical window, resulting in a decrease in gas generation and battery bank efficiency. The linear carbonate oxidation and decomposition on the positive electrode surface quickly exothermic heat, reducing calendar life and induced safety risks.

Method used

Lithium fluorosulfonimide is used as the lithium salt, combined with the first solvent as a linear carbonate containing ether bonds and the second solvent as a fluorolinear ether, an electrolyte system is formed. By controlling the proportion of the solvent and the content of lithium fluorosulfonimide, the electrochemical stability and thermal stability of the battery are significantly improved.

Benefits of technology

It significantly improves the battery's calendar life and safety performance, improves the battery's fast charging performance and rate performance, and reduces the reaction heat and improves the thermal stability of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852525A_ABST
    Figure CN119852525A_ABST
Patent Text Reader

Abstract

The invention relates to an electrolyte, a secondary battery and a device. The electrolyte comprises a lithium salt, an organic solvent and an additive, the lithium salt comprises fluorine-containing lithium sulfimide; the organic solvent comprises a first solvent and a second solvent, the first solvent is selected from at least one of compounds shown in a formula I, and the second solvent is selected from at least one of compounds shown in a formula II; # imgabs0 # wherein R1 and R3 are each independently selected from the group consisting of C1-C6 alkyl groups, and R2 is selected from the group consisting of C2-C6 alkylene groups; r < 4 > and R < 5 > are respectively and independently selected from fluorine substituted C < 1 >-C < 6 > alkyl groups; the electrolyte meets the condition that 6 < = 0.1 * A + 10 * B / C < = 45; wherein the DN value of the first solvent is A kcal / mol, and A is more than or equal to 20 and less than or equal to 50; based on the mass of the electrolyte, the mass percentage content of the first solvent is B, and the mass percentage content of the fluorine-containing lithium sulfimide is C. Therefore, the secondary battery electrolyte provided by the invention has at least one of the following advantages: excellent fast charging performance, electrochemical stability, thermal stability, calendar life and safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage, and in particular to an electrolyte, a secondary battery and a device. Background Art

[0002] Lithium-ion batteries have become a promising energy storage technology due to their advantages such as high energy density and long cycle life. However, they still have problems such as capacity decay during the cycle process and calendar aging, as well as thermal safety issues. In addition, battery components will inevitably age during long-term use. Therefore, studying the aging mechanism, reducing the aging rate, and avoiding safety risks are the key focuses of lithium-ion battery research.

[0003] Traditional commercial carbonate electrolytes are widely favored due to their high ionic conductivity and good lithium salt solubility. Carbonates, as electrolyte solvents, can be divided into cyclic carbonates and chain carbonates. Among them, cyclic carbonate solvents such as ethylene carbonate (EC) and propylene carbonate (PC) can dissociate more lithium salts and improve conductivity due to their high dielectric constants. They can also form a stable solid electrolyte interface film (SEI film) passivation layer during the formation stage to ensure that the battery has excellent cycle performance. In actual use, cyclic carbonates account for about 20 to 30 wt% of the solvent. Linear carbonate solvents such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) can provide suitable carriers for lithium insertion and extraction due to their low viscosity.

[0004] However, current electrolytes, secondary batteries, and devices still need to be improved. Summary of the invention

[0005] The inventors have found that the cyclic carbonates and linear carbonates used as electrolyte solvents in the prior art are still unable to effectively improve the calendar life and thermal runaway under high temperature conditions. This is mainly because the current electrolytes containing EC and PC cyclic carbonates are not friendly to negative electrode materials. The electrochemical window of EC and PC cyclic carbonates is narrow. Under high-temperature storage conditions, they will undergo reductive decomposition on the surface of the negative electrode with strong catalytic activity, resulting in gas generation and a decrease in the coulombic efficiency of the battery, which limits the long-term use of the battery components and causes inevitable safety problems. In addition, during the thermal abuse of battery cells, linear carbonates containing DMC, EMC, and DEC will undergo oxidative decomposition on the surface of the positive electrode with strong catalytic activity and rapidly release heat, resulting in a significant reduction in the battery calendar life. In view of this, in order to alleviate or solve at least one of the above-mentioned problems, the present application provides an electrolyte, a secondary battery and a device, wherein the lithium salt includes a fluorinated sulfonyl imide lithium, and the organic solvent includes a first solvent containing an ether bond linear carbonate (instead of cyclic carbonates EC, PC) and a second solvent fluorinated linear ether (instead of linear carbonates DMC, EMC, DEC). Compared with conventional cyclic carbonate and linear carbonate electrolytes, the electrolyte has a wide chemical window and high thermal stability, and the electrochemical stability and thermal stability are significantly improved, and the calendar life and safety performance of the battery are significantly improved.

[0006] On one hand, the present application provides an electrolyte, which includes: a lithium salt, an organic solvent and an additive; the lithium salt includes a fluorinated lithium sulfonyl imide; the organic solvent includes a first solvent and a second solvent, the first solvent is selected from at least one of the compounds shown in Formula I, and the second solvent is selected from at least one of the compounds shown in Formula II;

[0007] wherein R1 and R3 are each independently selected from C1-C6 alkyl; R2 is selected from C2-C6 alkylene; R4 and R5 are each independently selected from fluorine-substituted C1-C6 alkyl;

[0008] The electrolyte satisfies: 6≤0.1×A+10×B / C≤45;

[0009] Wherein, the DN value of the first solvent is A kcal / mol, 20≤A≤50;

[0010] Based on the mass of the electrolyte, the mass percentage content of the first solvent is B, and the mass percentage content of the fluorinated sulfonyl imide lithium is C.

[0011] On the other hand, the present application provides a secondary battery, which includes the electrolyte described above.

[0012] In another aspect, the present application provides a device, which includes the secondary battery described above.

[0013] The beneficial effects of this application are:

[0014] The lithium salt of the secondary battery electrolyte of the present application includes fluorinated lithium sulfonyl imide, and the organic solvent includes a first solvent containing ether bond linear carbonate (replacing cyclic carbonate EC, PC) and a second solvent fluorinated linear ether (replacing linear carbonate DMC, EMC, DEC). The fluorinated lithium sulfonyl imide, the ether bond linear carbonate solvent and the fluorinated linear ether solvent are combined to form an electrolyte system, and the DN value (Donor Number, donor number), the mass percentage content of the first solvent, and the mass percentage content of the fluorinated sulfonyl imide lithium can form a synergistic effect. On the one hand, through the above control, the electrochemical window of the ether-containing linear carbonate is wider than that of the cyclic carbonates EC and PC. After substitution, the battery calendar life and the chemical stability of the electrolyte during storage can be significantly improved. At the same time, its higher DN value can also increase the dissociation degree of the lithium salt, improve the conductivity, and increase the fast charging speed; and, the fluorinated linear ether has a wider electrochemical window than the linear carbonates DMC, DEC, and EMC. After substitution, it can limit the improvement of the chemical stability of the electrolyte during the thermal abuse of the battery. At the same time, during the calendar life storage process, it can reduce the loss of active lithium in the positive electrode and improve the calendar life. On the other hand, through the above control, the fluorinated sulfonyl imide lithium is used simultaneously with the above ether bond-containing linear carbonate and fluorinated linear ether. The fluorinated sulfonyl imide lithium is an imide lithium salt with nitrogen as the central atom. Due to its high degree of dissociation, it can significantly improve the conductivity of the electrolyte, thereby improving the fast charging performance of the battery, significantly improving the battery rate performance, and when used in combination with an organic solvent, it can form a loose, porous and stable SEI membrane interface structure, which is conducive to the rapid passage of lithium ions and improves the fast charging performance. The thermal decomposition temperature of the formed SEI membrane is increased, and the reaction heat can also be reduced, thereby improving the thermal stability of the electrolyte and the thermal stability of the interface. Based on the above improvements, the secondary battery electrolyte of the present application has at least one of the following advantages: excellent fast charging performance, electrochemical stability, thermal stability, calendar life and safety performance. DETAILED DESCRIPTION

[0015] For simplicity, this application only specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an undefined range; and any lower limit can be combined with other lower limits to form an undefined range, and any upper limit can be combined with any other upper limit to form an undefined range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an undefined range.

[0016] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).

[0017] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.

[0018] The term "C1-C6 alkyl" includes, but is not limited to, methyl, ethyl, n-propyl, isopropyl, cyclopropyl, butyl, pentyl, hexyl, and the like.

[0019] The term "C2-C6 alkylene" includes, but is not limited to, methylene, ethylene, n-propylene, isopropylene, butylene, pentylene, hexylene and the like.

[0020] The term "fluorine-substituted" means that the functional group described after the term is substituted with fluorine, and the number of substituents may be 1 or 2 or more.

[0021] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.

[0022] 1. Electrolyte

[0023] The electrolyte provided by the present application comprises: a lithium salt, an organic solvent and an additive; the lithium salt comprises a fluorinated lithium sulfonyl imide; the organic solvent comprises a first solvent and a second solvent, the first solvent is selected from at least one of the compounds shown in Formula I, and the second solvent is selected from at least one of the compounds shown in Formula II:

[0024] wherein R1 and R3 are each independently selected from C1-C6 alkyl; R2 is selected from C2-C6 alkylene; R4 and R5 are each independently selected from fluorine-substituted C1-C6 alkyl;

[0025] The electrolyte satisfies: 6≤0.1×A+10×B / C≤45; wherein the DN value of the first solvent is A kcal / mol, 20≤A≤50; based on the mass of the electrolyte, the mass percentage content of the first solvent is B, and the mass percentage content of the fluorinated sulfonyl imide lithium is C.

[0026] Thus, the lithium salt of the secondary battery electrolyte of the present application includes a fluorinated lithium sulfonyl imide, and the organic solvent includes a first solvent containing an ether bond linear carbonate (replacing the cyclic carbonate EC, PC) and a second solvent fluorinated linear ether (replacing the linear carbonate DMC, EMC, DEC), and the fluorinated lithium sulfonyl imide, the ether bond linear carbonate solvent and the fluorinated linear ether solvent are combined to form an electrolyte system, and the DN value of the first solvent, the mass percentage content of the first solvent, and the mass percentage content of the fluorinated lithium sulfonyl imide are controlled, and the DN value of the first solvent, the mass percentage content of the first solvent, and the mass percentage content of the fluorinated lithium sulfonyl imide are controlled. , can form a synergistic effect. On the one hand, through the above control, the electrochemical window of linear carbonates containing ether bonds is wider than that of cyclic carbonates EC and PC. After substitution, the battery calendar life and the chemical stability of the electrolyte during storage can be significantly improved. At the same time, its higher DN value can also increase the dissociation degree of lithium salts, improve conductivity, and increase fast charging speed; and, compared with linear carbonates DMC, DEC, and EMC, the electrochemical window of fluorinated linear ethers is wider. After substitution, it can limit and improve the chemical stability of the electrolyte during battery thermal abuse. At the same time, during the calendar life storage process, it can reduce the loss of active lithium in the positive electrode and improve the calendar life. On the other hand, through the above control, the fluorinated sulfonyl imide lithium is used simultaneously with the above ether bond-containing linear carbonate and fluorinated linear ether. The fluorinated sulfonyl imide lithium is an imide lithium salt with nitrogen as the central atom. Due to its high degree of dissociation, it can significantly improve the conductivity of the electrolyte, thereby improving the fast charging performance of the battery, significantly improving the battery rate performance, and when used in combination with an organic solvent, it can form a loose, porous and stable SEI membrane interface structure, which is conducive to the rapid passage of lithium ions and improves the fast charging performance. The thermal decomposition temperature of the formed SEI membrane is increased, and the reaction heat can also be reduced, thereby improving the thermal stability of the electrolyte and the thermal stability of the interface. Based on the above improvements, the secondary battery electrolyte of the present application has at least one of the following advantages: excellent fast charging performance, electrochemical stability, thermal stability, calendar life and safety performance.

[0027] In some embodiments, 6≤0.1×A+10×B / C≤45. In some embodiments, the value of 0.1×A+10×B / C is 6, 8, 10, 15, 20, 25, 30, 35, 40, 45 or any value therebetween. In some embodiments, 13≤0.1×A+10×B / C≤25. Thus, the battery calendar life and the chemical stability of the electrolyte during storage can be significantly improved, while also increasing the degree of dissociation of lithium salts, improving conductivity, and increasing the fast charging speed; and, during the calendar life storage process, it can reduce the loss of active lithium at the positive electrode and increase the calendar life. Through the above control, the electrolyte conductivity can be significantly improved, thereby improving the fast charging performance of the battery, significantly improving the battery rate performance, and forming a loose, porous and stable SEI film interface structure, which is conducive to the rapid passage of lithium ions, improving the fast charging performance, and the formed SEI film. The thermal decomposition temperature is increased, and the reaction heat can be reduced, thereby improving the thermal stability of the electrolyte and the thermal stability of the interface.

[0028] In some embodiments, the DN value of the first solvent is A kcal / mol, 20≤A≤50. In some embodiments, A is 20, 25, 28, 30, 32, 35, 40, 45, 50 or any value therebetween. In some embodiments, 30≤A≤40. It should be noted that the DN value is a measure of the ability of a solvent to dissolve cations. Thus, when the DN value of the first solvent is within the above range, the content of inorganic substances such as Li2O / LiF / Li2S in the interface that induces the generation of lithium salt anions increases, which promotes the increase of the inorganic content in the SEI film, can improve the stability of the SEI film, improve the calendar life, and improve the lithium ion transmission efficiency in the electrolyte, and the battery power performance is better. When the DN value is too high, inorganic substances such as Li2O / LiF / Li2S are more dissolved in the electrolyte, the inorganic content in the SEI film is reduced, the interface stability of the SEI film is reduced, and the calendar life is reduced. When the DN value is too low, the lithium salt anion cannot be induced to form a film, which weakens the interface passivation ability, thereby deteriorating the power performance and calendar life. In addition, the lithium ion transmission in the electrolyte with a low DN value is slower, and the battery power and cycle performance are deteriorated.

[0029] In some embodiments, based on the mass of the electrolyte, the mass percentage content of the first solvent is B, 5%≤B≤60%. In some embodiments, B is 5%, 10%, 20%, 30%, 40%, 50%, 60% or any value therebetween. In some embodiments, 15%≤B≤25%. As a result, the battery calendar life and the chemical stability of the electrolyte during storage can be significantly improved, while also increasing the degree of lithium salt dissociation, improving conductivity, and increasing fast charging speed. When the content of the first solvent is too large, the viscosity of the electrolyte will increase sharply, deteriorating the power and cycle performance; when the content of the first solvent is too small, the lithium ion transmission of the electrolyte will be too slow, thereby deteriorating the power and cycle performance.

[0030] In some embodiments, based on the mass of the electrolyte, the mass percentage content of the fluorinated sulfonyl imide lithium is C, 5%≤C≤20%. In some embodiments, C is 5%, 8%, 10%, 12%, 15%, 18%, 20% or any value therebetween. In some embodiments, 10%≤C≤15%. Thus, a loose, porous and stable SEI membrane interface structure can be formed, which is conducive to the rapid passage of lithium ions. When there is more LiFSI, more side reactions will be induced in the current collector, resulting in the accumulation of byproducts and hindering the transfer of lithium ions. When there is less LiFSI, the transmission resistance of lithium ions in the electrolyte body will increase, reducing the fast charging speed.

[0031] In some embodiments, the dielectric constant of the first solvent is 20 to 60. In some embodiments, the dielectric constant of the first solvent is 20, 30, 40, 50, 60 or any value therebetween. In some embodiments, the dielectric constant of the first solvent is 45 to 55.

[0032] In some embodiments, the fluorine-containing lithium sulfonyl imide includes at least one of lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethylsulfonyl imide (LiTFSI), lithium (fluorosulfonyl)(trifluoromethylsulfonyl)imide, lithium (fluorosulfonyl)(perfluorobutylsulfonyl)imide, lithium (trifluoromethylsulfonyl)(perfluorobutylsulfonyl)imide (LiFNFSI), and lithium bis(pentafluoroethylsulfonyl)imide (LiBETI). Therefore, fluorinated lithium sulfonyl imide is used simultaneously with the above-mentioned ether bond-containing linear carbonate and fluorinated linear ether. Fluorinated lithium sulfonyl imide is an imide lithium salt with nitrogen as the central atom. Due to its high degree of dissociation, it can significantly improve the conductivity of the electrolyte, thereby improving the fast charging performance of the battery and significantly improving the battery rate performance. When used in combination with an organic solvent, it can form a loose, porous and stable SEI film interface structure, which is conducive to the rapid passage of lithium ions and improves the fast charging performance. The thermal decomposition temperature of the formed SEI film is increased, the thermal stability of the interface is improved, and the reaction heat can be reduced, thereby improving the thermal stability of the electrolyte.

[0033] In some embodiments, the fluorinated lithium sulfonyl imide includes lithium bis(fluorosulfonyl) imide. Since the anion radius of LiFSI is large, it is easier to dissociate lithium ions, which can significantly improve the conductivity of the battery, thereby improving the fast charging performance of the battery, and at the same time, it can also improve the rate performance, safety, and high-temperature cycle stability of the secondary battery.

[0034] In some embodiments, R1 and R3 are each independently selected from C1-C3 alkyl; and R2 is selected from C2-C3 alkylene.

[0035] In some embodiments, R4 and R5 are each independently selected from fluorine-substituted C2-C4 alkyl.

[0036] In some embodiments, the first solvent is selected from at least one of the following compounds:

[0037]

[0038] Therefore, the electrochemical window of linear carbonates containing ether bonds is wider than that of cyclic carbonates EC and PC. After replacement, they can significantly improve the battery calendar life and the chemical stability of the electrolyte during storage. At the same time, their higher DN value can also increase the dissociation degree of lithium salts, improve conductivity, and increase fast charging speed.

[0039] In some embodiments, the second solvent is selected from at least one of the following compounds:

[0040]

[0041] Therefore, the electrochemical window of fluorinated linear ethers is wider than that of linear carbonates DMC, DEC, and EMC. After substitution, they can limit and improve the chemical stability of the electrolyte during battery thermal abuse. At the same time, during calendar life storage, they can reduce the loss of active lithium in the positive electrode and increase the calendar life.

[0042] In some embodiments, the organic solvent consists of the first solvent and the second solvent. Thus, the organic solvent includes a first solvent containing an ether bond linear carbonate (replacing cyclic carbonates EC, PC) and a second solvent fluorinated linear ether (replacing linear carbonates DMC, EMC, DEC). On the one hand, the electrochemical window of the ether bond linear carbonate is wider than that of the cyclic carbonates EC and PC. After replacement, the battery calendar life and the chemical stability of the electrolyte during storage can be significantly improved. At the same time, its high DN value can also increase the dissociation degree of lithium salts, improve conductivity, and increase fast charging speed. On the other hand, the electrochemical window of the fluorinated linear ether is wider than that of the linear carbonates DMC, DEC, and EMC. After replacement, the chemical stability of the electrolyte during the thermal abuse of the battery can be limited. At the same time, during the calendar life storage process, it can reduce the loss of active lithium at the positive electrode and increase the calendar life.

[0043] In some embodiments, the organic solvent also includes ethylene carbonate and propylene carbonate, and based on the mass of the electrolyte, the sum of the mass percentage content of ethylene carbonate and propylene carbonate is less than or equal to 5%. In some embodiments, the organic solvent also includes dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate, and based on the mass of the electrolyte, the sum of the mass percentage content of dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate is less than or equal to 5%. Thus, the organic solvent includes a first solvent containing ether bond linear carbonate (partially replacing cyclic carbonate EC, PC) and a second solvent fluorinated linear ether (partially replacing linear carbonate DMC, EMC, DEC). On the one hand, the electrochemical window of ether bond linear carbonate is wider than that of cyclic carbonate EC and PC. After replacement, the battery calendar life and the chemical stability of the electrolyte during storage can be significantly improved. At the same time, its higher DN value can also increase the dissociation degree of lithium salt, improve conductivity, and increase fast charging speed. On the other hand, fluorinated linear ethers have a wider electrochemical window than linear carbonates DMC, DEC, and EMC. After substitution, they can limit and improve the chemical stability of the electrolyte during battery thermal abuse. At the same time, during calendar life storage, they can reduce the loss of active lithium in the positive electrode and increase the calendar life.

[0044] In some embodiments, based on the mass of the electrolyte, the mass percentage content of the second solvent is 20% to 90%. In some embodiments, based on the mass of the electrolyte, the mass percentage content of the second solvent is 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or any value therebetween. In some embodiments, based on the mass of the electrolyte, the mass percentage content of the second solvent is 30% to 80%. As a result, the electrochemical window of the electrolyte is wider, which can limit and improve the chemical stability of the electrolyte during battery thermal abuse, and at the same time, during calendar life storage, it plays a role in reducing the loss of active lithium in the positive electrode and improving the calendar life.

[0045] In some embodiments, the additive includes vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate, 1,3-propane sultone, vinyl sulfate (DTD), 1,3-propene sultone, vinyl sulfite, tris(trimethylsilyl) phosphate (TMSP), tris(trimethylsilyl) borate (TMSB) and methylene disulfonate. In some embodiments, based on the mass of the electrolyte, the mass percentage content of the additive is 0.05% to 10%. In some embodiments, the mass percentage content of the additive is 0.05%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10% or any value therebetween. In some embodiments, the mass percentage content of the additive is 0.1% to 5%.

[0046] In some embodiments, the lithium salt further includes a first lithium salt, the first lithium salt including at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), trifluorosulfonyl lithium (LiTf), lithium bis(fluoromalonate) borate (LiBFMB), lithium difluorophosphate (LiDFP), lithium difluorooxalate borate (LiDFOB) and lithium dioxalate borate (LiBOB); based on the mass of the electrolyte, the mass percentage content of the first lithium salt is 0.05% to 20%. In some embodiments, the mass percentage content of the first lithium salt is 0.05%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or any value therebetween. In some embodiments, the mass percentage content of the first lithium salt is 1% to 15%.

[0047] 2. Secondary battery

[0048] In some embodiments, the secondary battery includes a positive electrode sheet, a negative electrode sheet, and the aforementioned electrolyte.

[0049] In some embodiments, the positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes at least one of a lithium nickel transition metal oxide and a phosphate material.

[0050] In some embodiments, the lithium nickel transition metal oxide comprises LiNi x M 1-x At least one of O2, M includes at least one of cobalt, manganese, iron, chromium, titanium, zinc, vanadium, aluminum, zirconium, cerium, magnesium, calcium, molybdenum, strontium, tungsten, yttrium, lanthanum, silver, niobium, copper and barium, 0.7≤x≤0.98. It is understood that all transition metal elements in the positive electrode active material include transition element nickel (Ni) and other transition elements M. The molar percentage content of the nickel element is based on the total molar amount of all transition metal elements (including transition element Ni and other transition elements M) in the positive electrode active material. In some embodiments, x is 0.7, 0.72, 0.74, 0.76, 0.78, 0.8, 0.82, 0.84, 0.86, 0.88, 0.9, 0.92, 0.94, 0.96, 0.98 or any value therebetween. In some embodiments, the positive electrode active material includes at least one of lithium nickel oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese cobalt magnesium oxide, and lithium nickel manganese oxide.

[0051] In some embodiments, the phosphate material includes LiMn k B (1-k) PO4, 0≤k≤1, B includes at least one of iron, cobalt, magnesium, calcium, zinc, chromium and lead. In some embodiments, k is 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95 or any value therebetween. In some embodiments, the phosphate includes at least one of lithium iron phosphate and lithium manganese iron phosphate. In some embodiments, the phosphate includes LiMn 0.6 Fe 0.4 PO4 and LiMn 0.8 Fe 0.2 At least one of PO4.

[0052] In some embodiments, the positive electrode active material layer further includes a binder, and optionally a conductive material. The binder improves the bonding of the positive electrode active material particles to each other and also improves the bonding of the positive electrode active material to the current collector.

[0053] In some embodiments, the binder includes: polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyacrylic acid (PAA), polymethyl methacrylate (PMMA), polyimide (PI), polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin or nylon, etc.

[0054] In some embodiments, the conductive material includes: a carbon-based material, a metal-based material, a conductive polymer, and a mixture thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.

[0055] In some embodiments, the positive electrode plate further includes a positive current collector, and the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used. The composite current collector may be obtained by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymer substrate.

[0056] In some embodiments, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes at least one of a carbon-based material, a silicon-based material, a tin-based material, a phosphorus-based material and metallic lithium; wherein the carbon-based material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes and graphene, the silicon-based material includes at least one of silicon, silicon alloy, silicon oxygen and silicon carbon, the tin-based material includes at least one of tin, tin oxide and tin alloy, and the phosphorus-based material includes phosphorus and / or phosphorus-carbon composites. In some embodiments, the negative electrode active material includes a carbon-based material and a silicon-based material. In some embodiments, based on the mass of the negative electrode active material layer, the mass percentage of the silicon-based material is 3% to 40%. In some embodiments, the mass percentage content of the silicon-based material is 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 25%, 30%, 35%, 40% or any value therebetween. In some embodiments, the negative electrode active material includes graphite, silicon oxide and / or silicon carbon, the silicon oxide can be ordinary silicon oxide (SiOx, 0.5≤x≤1.5), carbon-coated silicon oxide (SiOx / C) or carbon-coated pre-lithium silicon oxide (SiOx-Li / C), and the silicon carbon can be ground silicon carbon or deposited silicon carbon.

[0057] In some embodiments, the negative electrode active material layer further comprises a binder and a conductive agent. In some embodiments, the binder comprises: styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc.

[0058] In some embodiments, the conductive agent includes: a carbon-based material, a metal-based material, a conductive polymer, and a mixture thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.

[0059] In some embodiments, the negative electrode plate further includes a negative electrode current collector, and the negative electrode current collector includes: copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or any combination thereof.

[0060] In some embodiments, a separator is provided between the positive electrode plate and the negative electrode plate to prevent short circuit. The material and shape of the separator that can be used in the embodiments of the present application are not particularly limited, and it can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.

[0061] For example, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer includes at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be selected.

[0062] A surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.

[0063] The inorganic layer includes inorganic particles and a binder, wherein the inorganic particles include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene.

[0064] The polymer layer contains polymers, and the polymer material includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).

[0065] In some embodiments, the method for preparing the secondary battery includes providing an electrode assembly, injecting liquid, packaging and forming. In some embodiments, the temperature of the formation is 40°C to 50°C, for example, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C or 49°C.

[0066] In some embodiments, the formation comprises: charging to 4.25V at 0.05C current and standing for 60min at a temperature of 40°C-50°C, such as 45°C, and a pressure of 150kgf-250kgf, such as 210kgf, followed by charging to 4.25V at 0.1C, and then discharging to 3.0V at 0.2C.

[0067] In some embodiments, the secondary battery is a lithium secondary battery or a sodium secondary battery. In some embodiments, the lithium secondary battery includes: a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery.

[0068] In some embodiments, the secondary battery may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.

[0069] In some embodiments, the shape of the secondary battery is not particularly limited, and it can be cylindrical, square, or any other shape. In some embodiments, the secondary battery is a cylindrical battery.

[0070] In some embodiments, the present application further provides a battery module. The battery module includes the above-mentioned secondary battery. The battery module of the present application uses the above-mentioned secondary battery, and therefore has at least the same advantages as the secondary battery. The number of secondary batteries contained in the battery module of the present application can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.

[0071] In some embodiments, the present application further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0072] 3. Device

[0073] The present application also provides a device, which includes the secondary battery mentioned above.

[0074] In some embodiments, the device includes: an electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, a power storage system, etc. In order to meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module may be used.

[0075] In other embodiments, the device may be a mobile phone, a tablet computer, a laptop computer, etc. The device is usually required to be light and thin, and a secondary battery may be used as a power source.

[0076] Examples and Comparative Examples

[0077] Example 1

[0078] The preparation steps of the positive electrode plate are as follows: the positive electrode active material LiNi 0.9 Co 0.05 Mn 0.05 O2, CNT (conductive agent carbon nanotube) / acetylene black, binder polyvinylidene fluoride PVDF, by weight proportion LiNi 0.9 Co 0.05 Mn 0.05 O2: CNT / acetylene black: PVDF = 95: (2.0 / 1.0): 2 is fully homogenized in N-methylpyrrolidone NMP and coated on a 12 μm thick aluminum current collector, and then dried, rolled, hot pressed and other steps to obtain the positive electrode sheet.

[0079] The preparation steps of the negative electrode plate are as follows: add the negative electrode active material artificial graphite, the conductive agent acetylene black, the binder styrene-butadiene rubber SBR, the thickener sodium carboxymethyl cellulose CMCNa, and the polyacrylic acid PAA into deionized water in a weight ratio of 95:2:1.5:1:0.5, and after sufficient homogenization, coat it on an 8μm thick copper current collector, and then obtain the negative electrode plate through drying, rolling, hot pressing and other steps.

[0080] Preparation of electrolyte: In a glove box filled with argon (H2O < 0.1 ppm, O2 < 0.1 ppm), Japanese formula Ⅱ-1 The compounds are mixed, and then lithium bis(fluorosulfonyl)imide (LiFSI) and LiPF6, as well as additives of vinyl carbonate (VC) and vinyl sulfate (DTD) are slowly added to the mixed solution, and the electrolyte is obtained after stirring evenly, wherein the content of LiFSI is 10%, the content of the first solvent formula I-1 (DN value is 35) is 15%, the content of the second solvent formula II-1 is 73%, the content of VC is 0.5%, and the content of DTD is 1.5%.

[0081] Diaphragm: PP / PE / PP (polypropylene / polyethylene / polypropylene) three-layer composite diaphragm is used.

[0082] Preparation of lithium-ion secondary batteries: The positive electrode sheets, separators (PP / PE / PP three-layer composite films), and negative electrode sheets prepared above are overlapped in sequence, with the separator being located between the positive electrode sheets and the negative electrode sheets, and are wound to obtain bare cells. After being fully dried, the bare cells are placed in an aluminum-plastic film soft-package shell, and then the electrolyte prepared above is injected and sealed. After the battery is pre-charged, high-temperature infiltrated, formed (the formation conditions are: temperature 45°C, 0.05C current charged to 3V and then allowed to stand for 5 minutes, then 0.1C charged to 3.5V and then allowed to stand for 5 minutes, and then 0.33C charged to 4.0V) and high-temperature aging, it is subjected to constant capacity distribution.

[0083] Examples 2 to 9 and Comparative Examples 1 to 5

[0084] Examples 2 to 9 and Comparative Examples 1 to 5 are achieved by adjusting the types and contents of lithium salts, solvents and additives in the electrolyte on the basis of Example 1. Specific adjustment measures and detailed data are shown in Table 1.

[0085] Table 1

[0086]

[0087] Test Method

[0088] 1. DN value test

[0089] 23 Na NMR is used to calculate the DN value of the solvent. The solvent to be tested (e.g., compound I-1) is mixed with SbCl5 to form a 1:1 adduct, which is dispersed with 1,2-dichloroethane to form a 0.2 M mixed solution. 23 Na NMR test, compare the NMR shift test results with those of several known DN value solvents (e.g. acetone: 17; methanol: 19; tetrahydrofuran: 20) 23The Na NMR results are linearly fitted and the displacement values ​​are compared to obtain the DN value of the solvent to be tested. The unit is kilocalories per mole (kcal / mol). The DN value is a measure of the solvent's ability to dissolve cations and Lewis acids.

[0090] 2. Solvent dielectric constant ε test

[0091] The dielectric constant is obtained with the aid of a capacitance meter. The dielectric constant is a dimensionless value, and its calculation formula is ε=C / C0, where C0 is the capacitance value of the capacitor when air is the medium, and C is the capacitance value of the solvent.

[0092] 3. Positive electrode leakage current test

[0093] Charge the battery to 4.3V, remove the battery, and use an electrochemical workstation to test the current-time curve of the battery at a constant voltage of 4.3V. After 12 hours, read the output current value, which is the leakage current of the battery positive electrode.

[0094] 4. Capacity retention rate test

[0095] At 25°C, the prepared lithium-ion secondary battery was charged to 4.2V at a constant current rate of 1C, and then charged at a constant voltage until the current was less than 0.05C. After standing for 5 minutes, it was discharged to 2.5V at a rate of 1C, and the initial discharge capacity was recorded. The lithium-ion secondary battery was charged and discharged 500 times by the above method, and the discharge capacity was recorded each time. The capacity retention rate of the lithium-ion secondary battery after 300 cycles at 25°C = the discharge capacity of the 300th time / initial discharge capacity × 100%.

[0096] At 45°C, the prepared lithium-ion secondary battery was charged to 4.2V at a constant current rate of 1C, and then charged at a constant voltage until the current was less than 0.05C. After standing for 5 minutes, it was discharged to 2.5V at a rate of 1C, and the initial discharge capacity was recorded. The lithium-ion secondary battery was charged and discharged 200 times by the above method, and the discharge capacity was recorded each time. The capacity retention rate of the lithium-ion secondary battery after 200 cycles at 45°C = the discharge capacity of the 200th time / initial discharge capacity × 100%.

[0097] 5. Storage capacity retention rate test at 45℃

[0098] At 45°C, the prepared lithium-ion secondary battery was charged to 4.2V at a constant current rate of 1C, and then charged at a constant voltage until the current was less than 0.05C. After standing for 5 minutes, it was discharged to 2.5V at a rate of 1C, and the initial discharge capacity was recorded. The lithium-ion secondary battery was charged and discharged 300 times using the above method, and the discharge capacity of each time was recorded. The capacity retention rate of the lithium-ion secondary battery after 300 cycles at 45°C = the discharge capacity of the 300th time / initial discharge capacity × 100%, and then stored at 45°C for 14 days / 30 days / 60 days to record the 0.33C discharge capacity of the battery. The storage capacity retention rate = the discharge capacity after the Nth storage / initial discharge capacity × 100%.

[0099] 6. Battery hot box test

[0100] The hot box test steps are as follows:

[0101] Calibration & full charge: no need to install fixture;

[0102] 1-1) 25±2℃, let stand for 5min;

[0103] 1-2) 25±2℃, charge to 4.25V with 1 / 3C rated CC-CV, and the cut-off current is 1 / 20C rated;

[0104] 1-3) 25±2℃, let stand for 30min;

[0105] 1-4) 25±2℃, discharge to 2.5V at 1 / 3C;

[0106] 1-5) 25±2℃, stand for 30min;

[0107] 1-6) Repeat steps 1-2) to 1-5); (take the second week calibration discharge capacity as C real);

[0108] 1-7) 25±2℃, charge to 4.25V with 1 / 3C rated CC-CV, and the cut-off current is 1 / 20C rated;

[0109] 1-8) End;

[0110] Cell information collection before testing: cell open circuit voltage, ACR, weight and status photos;

[0111] Test-hot box: battery cell upper fixture, preload 1.5Nm, 6 bolts;

[0112] 2-1) The battery is placed in a temperature box, and the temperature box is raised from ambient temperature to 130±2℃ at a rate of 5℃ / min, and this temperature is maintained for 60 minutes;

[0113] 2-2) The temperature box continues to increase by 10°C at a rate of 5°C / min and maintains this temperature for 60 minutes;

[0114] 2-3) Repeat steps 1-2) until the system loses control.

[0115] Test Results

[0116] Table 2

[0117]

[0118] It can be seen from Examples 1 to 9 and Comparative Examples 1 to 5 that by simultaneously adding fluorinated sulfonyl imide lithium and ether-bonded linear carbonate solvents to the electrolyte, and by controlling the DN value of the first solvent, the mass percentage content of the first solvent, and the mass percentage content of fluorinated sulfonyl imide lithium, a synergistic effect can be formed. On the one hand, the battery calendar life and the chemical stability of the electrolyte during storage can be improved, and the degree of dissociation of lithium salts can be increased, the conductivity can be improved, and the fast charging speed can be increased; and the chemical stability of the electrolyte during the thermal abuse of the battery can be limited, and during the calendar life storage process, the loss of active lithium at the positive electrode can be reduced and the calendar life can be improved. On the other hand, the electrolyte conductivity can be significantly improved, thereby improving the fast charging performance of the battery, significantly improving the battery rate performance, and forming a loose, porous and stable SEI membrane interface structure, which is conducive to the rapid passage of lithium ions, improving the fast charging performance, and the thermal decomposition temperature of the formed SEI membrane is increased, and the reaction heat can be reduced, thereby improving the thermal stability of the electrolyte and the thermal stability of the interface.

[0119] By comparing Comparative Examples 1 to 5 and Examples 1 to 9, it can be seen that when the first solvent (containing ether-bonded linear carbonate) is not added to the electrolyte, the first solvent content is too low or too high, and the LiFSI content is too low or too high, the performance of the secondary battery will be affected, such as increased leakage current, poor capacity retention rate, poor battery recovery rate, low hot box test temperature, etc.

[0120] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims.

Claims

1. An electrolyte, characterized in that: include: Lithium salts, organic solvents and additives; The lithium salt includes fluorinated lithium sulfonyl imide; The organic solvent includes a first solvent and a second solvent, the first solvent is selected from at least one of the compounds shown in Formula I, and the second solvent is selected from at least one of the compounds shown in Formula II: R4-O-R5 formula II; wherein R1 and R3 are each independently selected from C1-C6 alkyl, R2 is selected from C2-C6 alkylene; R4 and R5 are each independently selected from fluorine-substituted C1-C6 alkyl; The electrolyte satisfies: 6≤0.1×A+10×B / C≤45; Wherein, the DN value of the first solvent is A kcal / mol, 20≤A≤50; Based on the mass of the electrolyte, the mass percentage content of the first solvent is B, and the mass percentage content of the fluorinated sulfonyl imide lithium is C.

2. The electrolyte according to claim 1, characterized in that 13≤0.1×A+10×B / C≤25; and / or, 30≤A≤40; and / or, 5%≤B≤60%; and / or, 5%≤C≤20%.

3. The electrolyte according to claim 2, characterized in that 15%≤B≤25%; and / or, 10%≤C≤15%; and / or, the dielectric constant of the first solvent is 20-60.

4. The electrolyte according to any one of claims 1 to 3, characterized in that The fluorine-containing lithium sulfonyl imide comprises at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium (fluorosulfonyl)(trifluoromethylsulfonyl)imide, lithium (fluorosulfonyl)(perfluorobutylsulfonyl)imide, lithium (trifluoromethylsulfonyl)(perfluorobutylsulfonyl)imide and lithium bis(pentafluoroethylsulfonyl)imide; and / or R1 and R3 are each independently selected from C1-C3 alkyl, and R2 is selected from C2-C3 alkylene; and / or R4 and R5 are each independently selected from fluorine-substituted C2-C4 alkyl groups.

5. The electrolyte according to claim 4, characterized in that The fluorine-containing lithium sulfonyl imide comprises lithium bis(fluorosulfonyl)imide; and / or The first solvent is selected from at least one of the following compounds: The second solvent is selected from at least one of the following compounds: The organic solvent consists of the first solvent and the second solvent.

6. The electrolyte according to claim 1 or 2, characterized in that: The organic solvent further comprises ethylene carbonate and propylene carbonate, and based on the mass of the electrolyte, the sum of the mass percentages of the ethylene carbonate and the propylene carbonate is less than or equal to 5%; and / or The organic solvent further comprises dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate, and based on the mass of the electrolyte, the sum of the mass percentage contents of dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate is less than or equal to 5%; and / or Based on the mass of the electrolyte, the mass percentage content of the second solvent is 20% to 90%.

7. The electrolyte according to claim 6, characterized in that Based on the mass of the electrolyte, the mass percentage content of the second solvent is 30% to 80%; and / or The additives include vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, 1,3-propane sultone, vinyl sulfate, 1,3-propene sultone, vinyl sulfite, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate and methylene methanedisulfonate; based on the mass of the electrolyte, the mass percentage content of the additives is 0.05% to 10%; and / or The lithium salt also includes a first lithium salt, which includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, trifluorosulfonyl lithium and lithium bis(fluoromalonate)borate; based on the mass of the electrolyte, the mass percentage content of the first lithium salt is 0.05% to 20%.

8. A secondary battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet and an electrolyte as claimed in any one of claims 1 to 7.

9. The secondary battery according to claim 8, characterized in that: The positive electrode sheet comprises a positive electrode active material layer, the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises at least one of a lithium nickel transition metal oxide and a phosphate material; wherein the lithium nickel transition metal oxide comprises LiNi x M 1-x O2, M includes at least one of cobalt, manganese, iron, chromium, titanium, zinc, vanadium, aluminum, zirconium, cerium, magnesium, calcium, molybdenum, strontium, tungsten, yttrium, lanthanum, silver, niobium, copper and barium, 0.7≤x≤0.98; the phosphate material includes LiMn k B (1-k) PO4, 0≤k≤1, B comprises at least one of iron, cobalt, magnesium, calcium, zinc, chromium and lead; and / or The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes at least one of a carbon-based material, a silicon-based material, a tin-based material, a phosphorus-based material and metallic lithium; wherein the carbon-based material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes and graphene, the silicon-based material includes at least one of silicon, silicon alloy, silicon oxygen and silicon carbon, the tin-based material includes at least one of tin, tin oxide and tin alloy, and the phosphorus-based material includes phosphorus and / or a phosphorus-carbon composite.

10. A device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 8 to 9.